Psychologists' engagement in reflective practice and experiences of burnout: a correlational analysis. Issue 5 (3rd September 2022) - Sadusky, Andrea; Spinks, Jacob
ABSTRACT: Psychologists are prone to experiences of burnout due to the nature of their work. They are encouraged to engage in reflective practice for gaining self-awareness, such as when their psychological wellbeing is having an impact on their ability to effectively work with clients. This study was the first to investigate the relationships between psychologists' burnout levels and reflective practices. Psychologists from Australia ( n = 110) and other countries ( n = 10) completed the Copenhagen Burnout Inventory (CBI), Reflective Practice Questionnaire (RPQ), and Depression Anxiety Stress Scale – Short Form (DASS-21) in an online survey. The correlations between the CBI and RPQ scales were examined. Pre-liminary screening revealed the general mental health of the sample was normal. Two of the 10 RPQ domains were correlated with personal-, work-, and/or client-related burnout: Stress Interacting with Clients and Job Satisfaction. This study illuminated the importance of adequate supervision for psychologists to support their ability to manage their workloads, and wellbeing in the workplace. Person-centered and systemic approaches for addressing RP and burnout in the field of psychology are critical.